Educandy Website As An Evaluation Tool In Learning Tarkib Nahwu Grade V Students - Harsita, Destia; Triwibowo, Muhammad; Huda, Miftahul; Machmudah, Umi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This research aims to find out 1). steps for using the Educandy Website as a tool for evaluating Tarkib Nahwu learning 2). Effectiveness of the Educandy Website as an evaluation tool for teaching and learning Nahwu. This research uses a mixed method, namely a combination of quantitative and qualitative methods. The data collection techniques used are documentation and questionnaires. The results of this research show the steps for using the Educandy Website as an evaluation tool for teaching and learning nahwu, which is supported by three features, namely words, machtingmatchingand quiz questions. Meanwhile, learning Arabic through the Educandy website can support the Tarkib Nahwu learning process very effectively. This is proven by the questionnaire distributed via Google Forms which received a score of 80%. Keywords: Evaluation, Educandy Website, Tarkib Nahwu